Pharmacogene Variation in Thai Plasmodium vivax Relapse Patients Treated with a Combination of Primaquine and Chloroquine - Chamnanphon M; Gaedigk A; Puangpetch A; Pasomsub E; Chantratita W; Longley RJ; Sattabongkot J; Chariyavilaskul P; Sukasem C (Dove Medical Press, 2020)
Monpat Chamnanphon, 1 Andrea Gaedigk, 2 Apichaya Puangpetch, 3, 4 Ekawat Pasomsub, 5 Wasun Chantratita, 6 Rhea J Longley, 7, 8 Jetsumon Sattabongkot, 7 Pajaree Chariyavilaskul, 1 Chonlaphat Sukasem 3, 4 1Clinical Pharmacokinetics and Pharmacogenomics Research Unit, Department of Pharmacology, Faculty of Medicine, Chulalongkorn University, Bangkok 10330, Thailand; 2Division of Clinical Pharmacology, Toxicology & Therapeutic Innovation, Children’s Mercy Kansas City, and School of Medicine, University of Missouri-Kansas City, Kansas City, MO, USA; 3Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 4Laboratory for Pharmacogenomics, Somdech Phra Debaratana Medical Center (SDMC), Ramathibodi Hospital, Bangkok, Thailand; 5Division of Virology, Department of Pathology, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 6Center of Genomics Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 7Mahidol Vivax Research Unit, Faculty of Tropical Medicine, Mahidol University, Bangkok, Thailand; 8Walter and Eliza Hall Institute of Medical Research, Melbourne, VIC, Australia; Department of Medical Biology, University of Melbourne, Melbourne, VIC, AustraliaCorrespondence: Chonlaphat SukasemDivision of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandTel +66 22004330-2Fax +66 22004332Email chonlaphat.suk@mahidol.ac.thPurpose: Pharmacogenes have an influence on biotransformation pathway and clinical outcome of primaquine and chloroquine which are often prescribed to treat Plasmodium vivax infection. Genetic variation may impact enzyme activity and/or transporter function and thereby contribute to relapse. The aim of the study was to assess allele, genotype frequencies and the association between pharmacogenes variation and primaquine response in Thai patients infected with Plasmodium vivax.Patients and Methods: Fifty-one patients were genotyped for 74 variants in 18 genes by Sequenom MassARRAY® and Taqman® SNP Real-Time PCR.Results: SNP frequencies were not significantly different between relapse (n=4) and non-relapse (n=47) patients. However, the CYP2C19 c.681G>A, the frequency of the A-allele that defines the non-functional CYP2C19*2 haplotype was significantly higher compared to the G-allele (OR=5.14, p=0.021). Patients heterozygous for ABCG2 c.421C>A had a higher odds ratio (OR=8.75, p=0.071) and the frequency of the G-allele of UGT2B7 c.372G>A was higher compared to the A-allele (OR=3.75, p=0.081). CYP2C19, ABCG2 and UGT2B7 emerged as potential high priority genes.Conclusion: Decreased activity of CYP2C19, ABCG2 and UGT2B7 in combination with CYP2D6 intermediate or poor metabolizer status may expose patients to a higher risk of Plasmodium vivax relapse. Further investigations are warranted to substantiate these findings.Keywords: primaquine, chloroquine, Plasmodium vivax, relapse, pharmacogenes